Interrelationships between snowpack dynamics and tree growth in the Tigiretsky Ridge (Altai): Implications for ecological responses to climate variability - Nikolay I. Bykov; Roman Ju. Birjukov (Acta Biologica Sibirica)
This study examines the complex interplay between snowpack dynamics and tree growth in the Tigiretsky Ridge region, utilizing a combination of tree-ring chronologies and snowpack data from 2013 to 2020. Employing the Temperature-Based Melt-Index Method, we accurately assessed the maximum snowpack water equivalent during winter months, revealing significant spatial variability influenced by elevation, slope aspect, and proximity to watersheds. Our findings indicate an asymmetrical distribution of snow cover, with higher snow reserves on the southern slopes at lower elevations and a reversal at higher altitudes. Notably, near watershed areas, snow reserves on the northern slope can exceed those on the southern slope by a factor of 30. The analysis also highlights the positive correlation between increased snowpack water equivalent and radial growth of Abies sibirica L. within the ecotone of the upper timberline, suggesting a significant ecological response to changing snow conditions. These insights contribute to a deeper understanding of how climate variability impacts snow-vegetation interactions in mountainous ecosystems, laying the groundwork for future research aimed at unraveling the underlying mechanisms of these relationships.